Low phosphate represses histone deacetylase complex1 to regulate root system architecture remodeling in Arabidopsis. Issue 4 (15th November 2019) - Xu, Jia Meng; Wang, Zhan Qi; Wang, Jia Yi; Li, Peng Fei; Jin, Jian Feng; Chen, Wei Wei; Fan, Wei; Kochian, Leon V.; Zheng, Shao Jian; Yang, Jian Li
Summary: The mechanisms involved in the regulation of gene expression in response to phosphate (Pi) deficiency have been extensively studied, but their chromatin‐level regulation remains poorly understood. We examined the role of histone acetylation in response to Pi deficiency by using the histone deacetylase complex1 ( hdc1 ) mutant. Genes involved in root system architecture (RSA) remodeling were analyzed by quantitative real‐time polymerase chain reaction (qPCR) and chromatin immunoprecipitation qPCR. We demonstrate that histone H3 acetylation increased under Pi deficiency, and the hdc1 mutant was hypersensitive to Pi deficiency, with primary root growth inhibition and increases in root hair number. Concomitantly, Pi deficiency repressed HDC1 protein abundances. Under Pi deficiency, hdc1 accumulated higher concentrations of Fe 3+ in the root tips and had higher expression of genes involved in RSA remodeling, such as ALUMINUM‐ACTIVATED MALATE TRANSPORTER1 ( ALMT1 ), LOW PHOSPHATE ROOT1 ( LPR1 ), and LPR2 compared with wild‐type plants. Furthermore, Pi deficiency enriched the histone H3 acetylation of ALMT1 and LPR1 . Finally, genetic evidence showed that LPR1/2 was epistatic to HDC1 in regulating RSA remodeling. Our results suggest a chromatin‐level control of Pi starvation responses in which HDC1‐mediated histone H3 deacetylation represses the transcriptional activation of genes involved in RSA remodeling in Arabidopsis .